Implementasi Kurikulum 2013 Revisi Dalam Mengembangkan Kognitif Siswa Pada Mata Pelajaran Akidah Akhlak Kelas IX Di MTs Teladan Gebang - Nurul Hasanah, Usmaidar, Nurmisdaramayani (Pusdikra Publishing, 2023)
To find out the implementation of the revised 2013 curriculum in MTs. Gebang's example. To find out the implementation of the revised 2013 curriculum in improving students' cognitive abilities, especially in the Aqidah Akhlak subject at MTs. Gebang's example.. To find out the implementation of the 2013 curriculum for the acquisition of student learning completeness results in the class IX class Aqidah Akhlak subject at MTs. Gebang's example. Field research was used to obtain the data needed in this study, namely by using data collection tools through observation, interviews or structured interviews, and documentation. The data obtained was then processed and analyzed. In this study, qualitative research was used with an analytical description approach, namely by describing the research results obtained through structured interviews on research sources. The results of the study Cognitive improvement efforts using the K13 curriculum in the Akidah Akhlak subject at Teladan Gebang MTs were carried out by involving all students to be active through different assignments for each group where there were groups of questioners, groups that agreed, groups that did not agree, groups gave examples, and group summarizes. Cognitive improvement efforts using the K13 curriculum in the Aqidah subject have been able to increase student activity although there are still visible differences between students who are active and students who are less active. Efforts to improve cognitive use of the K13 curriculum in the Aqidah subject have been able to increase students' understanding of the subject matter taught in learning activities. The obstacle is that some students still do not understand the learning system using the K13 curriculum, so they have to be more extra in providing instruction and guidance to students. The solution given, as a teacher, should have a way to make students not get bored easily in participating in teaching and learning activities. Have good skills and master several techniques in teaching. Then teach students to be more active and creative and easy to work with their classmates, and make it easier for students to improve cognitive when learning the Aqidah Akhlak.